Eschatology and the New Testament essays in honour of George Raymond Beasley-Murray - Beasley-Murray, George Raymond, 1916-2000; Gloer, W. Hulitt (Peabody, MA Hendrickson, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- escatology